Artistic transformation of Martin Heidegger's hermeneutic concepts in the lyrics of Igor Rymaruk (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article analyses the motive of creativity and the image of the Poet in Igor Rimaruk’s lyrics, the representative of the poetic generation of the 1980s. The theoretical basis for the study was Martin Heidegger’s hermeneutical concepts expressed in the works «Why do poets?», «Helderlin and the essence of the poetry». Dramatic colisees and internal conflicts of the motive of creativity have been Illuminated in I. Rimaruk’s poetical collections, caused by the myth of the «accursed poet», which has long traditions in the Ukrainian literature. The ontological regularities have been thoroughly examined in the functioning of the philosophic concept of the individual alienation from the world and his influence on the modelling of the author's world picture. The main attention has been paid to the opening of existential lyrics discourse, connected with the loneliness existential, alienation of the individual from the world and others. The hermeneutic dialogue of I. Rymaruk’s lyrics with the philosophical ideas of M. Heidegger is based on the discussion about the dominant role of the ideological or aesthetic function of creativity The lyrics of I. Rymaruk in the aesthetic plane polemicises around the eternal dilemma: the real Poet must be a Prophet or uphold the ideas of «pure lyrics» – stay in the world of beauty and art The opposition «damned poet» / «real poet» has been analysed through the prism of the Heidegger’s concept of the language essence of literary works. The artistic peculiarity of poetic texts is analysed. The aesthetic originality of philosophical motives on the material of I. Rymaruk's poetic collections «The Tear of the Virgin», «Divine Wind» has been determined. A comparative analysis of Igor Rymaruk’s poetry has been made with the typologically similar lyrics of the Prague School representatives – Oleg Olzhich and Eugene Malanyuk. The artistic peculiarity of the poetry has been defined. The line of expressive means which are typical for the poet has been characterised: psychologism, meditativity, contrast, metaphorism.
Keywords: lyrics; stylet; stylos; hermeneutical concepts; lyrical subject; motive; metaphoric image